2017
DOI: 10.1101/110163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cas9-Assisted Targeting of CHromosome segments (CATCH) for targeted nanopore sequencing and optical genome mapping

Abstract: Variations in the genetic code, from single point mutations to large structural or copy number alterations, influence susceptibility, onset, and progression of genetic diseases and tumor transformation. Next-generation sequencing analysis is unable to reliably capture aberrations larger than the typical sequencing read length of several hundred bases. Long-read, singlemolecule sequencing methods such as SMRT and nanopore sequencing can address larger variations, but require costly whole genome analysis. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The level of enrichment by Xdrop technology is comparable to other long-read targeted enrichment strategies (Gabrieli et al, 2017;Gilpatrick et al, 2019;Tsai et al, 2017) interest, and they require micrograms of input DNA (Gilpatrick et al, 2019;Hoijer et al, 2018;Stangl et al, 2019;Tsai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The level of enrichment by Xdrop technology is comparable to other long-read targeted enrichment strategies (Gabrieli et al, 2017;Gilpatrick et al, 2019;Tsai et al, 2017) interest, and they require micrograms of input DNA (Gilpatrick et al, 2019;Hoijer et al, 2018;Stangl et al, 2019;Tsai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our MT platform is well suited to this dual analysis in the same single molecules of DNA. To analyze specific gene loci without DNA amplification, we developed the CRISPR/Cas9 enrichment method that achieved target specificities that are far greater than we have seen reported elsewhere in the published literature [10][11][12] . From human genomic DNA, we enriched fragments containing FMR1 and observed that the allele frequency of expanded repeats to normal was in the expected 1:1 ratio for a heterozygous sample.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to full genome sequencing, these protocols dramatically reduce per-sample costs as multiple samples can be pooled and multiplexed; however, because these methods involve sample amplification, this benefit comes at the penalty of loss of epigenetic information and the introduction of bias into the results 9 . Recently amplification-free Cas9-based enrichment strategies have been attempted by several groups [10][11][12] but typically only achieve an enrichment of 20-to 60-fold (compared to 10,000-fold for PCR) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…250 Cas9 may also be useful to directly enrich for desired sequences, either through dCas9-based affinity purification or through the excision and subsequent isolation of genomic regions of interest. 251 Cas9 has even proven useful for physical mapping of genomic DNA. In one study, a Cas9 mutant was used to nick specific genomic sequences, followed by DNA polymerase-mediated local incorporation of fluorescent nucleotides; the resulting sites could then be directly visualized within nanochannel arrays using fluorescence microscopy to identify structural variants.…”
Section: Crispr-based Biochemical Toolsmentioning
confidence: 99%